Changes in the transcriptome of the malaria parasite Plasmodium falciparum during the initial phase of transmission from the human to the mosquito - Ngwa, Che Julius (BioMed Central, 2013)
BACKGROUND: The transmission of the malaria parasite Plasmodium falciparum from the human to the mosquito is mediated by dormant sexual precursor cells, the gametocytes, which become activated in the mosquito midgut. Because gametocytes are the only parasite stages able to establish an infection in the mosquito, they play a crucial role in spreading the tropical disease. The human-to-mosquito transmission triggers important molecular changes in the gametocytes, which initiate gametogenesis and prepare the parasite for life-cycle progression in the insect vector. RESULTS: To better understand gene regulations during the initial phase of malaria parasite transmission, we focused on the transcriptome changes that occur within the first half hour of parasite development in the mosquito. Comparison of mRNA levels of P. falciparum gametocytes before and 30 min following activation using suppression subtractive hybridization (SSH) identified 126 genes, which changed in expression during gametogenesis. Among these, 17.5% had putative functions in signaling, 14.3% were assigned to cell cycle and gene expression, 8.7% were linked to the cytoskeleton or inner membrane complex, 7.9% were involved in proteostasis and 6.4% in metabolism, 12.7% were cell surface-associated proteins, 11.9% were assigned to other functions, and 20.6% represented genes of unknown function. For 40% of the identified genes there has as yet not been any protein evidence. For a subset of 27 genes, transcript changes during gametogenesis were studied in detail by real-time RT-PCR. Of these, 22 genes were expressed in gametocytes, and for 15 genes transcript expression in gametocytes was increased compared to asexual blood stage parasites. Transcript levels of seven genes were particularly high in activated gametocytes, pointing at functions downstream of gametocyte transmission to the mosquito. For selected genes, a regulated expression during gametogenesis was confirmed on the protein level, using quantitative confocal microscopy. CONCLUSIONS: The obtained transcriptome data demonstrate the regulations of gene expression immediately following malaria parasite transmission to the mosquito. Our findings support the identification of proteins important for sexual reproduction and further development of the mosquito midgut stages and provide insights into the genetic basis of the rapid adaption of Plasmodium to the insect vector.